Twice‐refocused stimulated echo diffusion imaging: Measuring diffusion time dependence at constant T1 weighting. Issue 5 (28th October 2019) - Martin, Jan; Endt, Sebastian; Wetscherek, Andreas; Kuder, Tristan Anselm; Doerfler, Arnd; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd
Abstract : Purpose: Diffusion times longer than 50 ms are typically probed with stimulated‐echo sequences. Varying the diffusion time in stimulated‐echo sequences affects the T 1 weighting of subcompartments, complicating the analysis of diffusion time dependence. Although inversion recovery preparation could be used to change the T 1 weighting, it cannot ensure equal T 1 weighting at arbitrary mixing times. In this article, a sequence that ensures constant T 1 weighting over a wide range of diffusion times is presented. Methods: The proposed sequence features 2 independent longitudinal storage periods: TM1 and TM2 . Diffusion encoding is performed during TM1, effectively coupling the diffusion time and TM1 . Equal T 1 weighting at arbitrary diffusion times is realized by keeping the total mixing time TM1 + TM2 constant. The sequence was compared with conventional stimulated‐echo measurements of diffusion in a 2‐compartment phantom consisting of distilled water and paraffinum perliquidum. Additionally, in vivo DTI of the brain was carried out for 8 healthy volunteers with diffusion times ranging from 50 to 500 ms. Results: Diffusion time dependence of the axial and radial diffusivity was detected in the brain. Both sequences resulted in almost identical diffusivities in white matter. In regions containing partial volumes of gray and white matter, a dependency on T 1 weighting was observed. Conclusion: In accordance with previous studies, little variance of T 1 values appeared to be present in healthy white matter. However, this is likely different in diseased tissue. Here, the proposed sequence can be effective in differentiating between diffusion time dependence and T 1 weighting effects.